Texte littéraire dans la glottodidactique - Antkowiak, Krystyna (Glottodidactica, 1999)
Reading in a foreign language is a skill which is important for an overall competence. The researches done in the 1980s and the 1990s proved the utility of the text and especially of the literary one in language teaching. The present article deals with the use of self instruction in language teaching. Self instruction aims not only at giving a learner some knowledge but also at making him able to leam by himself and at giving him an attitude of independence towards the society he lives in, which is possible only when he is aware of how a society works. Reading itself is an autonomous activity because it is a self-directed process of discovering the meaning of a text. In order to make this process efficient a leamer-reader should leam some strategies which will enable him not to use a dictionary too often. Tasks in relation to reading texts should lead a learner to think over the meaning of the text, to compare his opinions with those of the author, to speak about his reactions. And last but not least: reading literary works makes a learner get acquainted with the culture of people whose language he is learning.